Uporaba vitamina A v dermatologiji in njegova toksičnost - Savić, Marko (Placebo, 2025)
Vitamin A encompasses a group of fat-soluble compounds collectively known as retinoids, which include both natural and synthetic forms. These compounds play a vital role in maintaining skin health, regulating cell proliferation and diff erentiation, and supporting immune function. In dermatology and cosmetics, retinoids are extensively used for their effi cacy in promoting collagen synthesis, accelerating epidermal turnover, and improving skin texture, tone, and pigmentation. Despite their benefi ts, vitamin A compounds can induce both systemic and local toxicity when used improperly. Topical application, though generally safer, can still cause retinoid dermatitis which disrupts the skin’s barrier function. These eff ects arise from interactions with nuclear receptors (RAR and RXR), which infl uence gene expression. Due to their high biological activity and the risk of systemic absorption, particularly in pregnant women, strict concentration limits have been set by regulatory authorities to ensure safe use in cosmetic and therapeutic products.
Keywords: Dermatologija; dermatology; fotosenzitivnost; photosensitivity; retinoidi; retinoids; teratogenicity; teratogenost; toksičnost; topical use; topikalna uporaba; toxicity; vitamin A; Vitamini